Population pharmacokinetic modelling of febuxostat in healthy subjects and people with gout. Issue 12 (28th July 2022) - Kamel, Bishoy; Abuhelwa, Ahmad Y.; Foster, David; Duong, Janna K.; Graham, Garry G.; Williams, Kenneth M.; Pile, Kevin D.; Day, Richard O.
Abstract : Aims: To investigate and characterise the pharmacokinetics of febuxostat and the effect of the covariates of renal function and body size descriptors on the pharmacokinetics of the drug. Methods: Blood samples (n = 239) were collected using sparse and rich sampling strategies from healthy (n = 9) and gouty (n = 29) subjects. Febuxostat plasma concentrations were measured by a validated high‐performance liquid chromatography method. Population pharmacokinetic analysis was performed using NONMEM. A common variability on bioavailability (FVAR) approach was used to test the effect of fed status on absorption parameters. Covariates were modelled using a power model. Results: The time course of the plasma concentrations of febuxostat is best described by a two‐compartment model. In the final model, the population mean for apparent clearance (CL/F), apparent central volume of distribution (Vc/F), apparent peripheral volume of distribution (Vp/F), absorption rate constant (ka) and apparent intercompartmental clearance (Q/F) were 6.91 l h −1, 32.8 l, 19.4 l, 3.6 h −1 and 1.25 l h −1, respectively. The population parmater variability (coefficient of variation) for CL/F, Vc/F and Vp/F were 13.6, 22 and 19.5%, respectively. Food reduced the relative biovailability and ka by 67% and 87%, respectively. Renal function, as assessed by creatinine clearance, was a significant covariate for CL/F while body mass index was a significant covariate for Vc/F. Conclusions: Renal function and body mass index were significant covariates. Further work is warranted to investigate the clinical relevance of these results, notably as renal impairment and obesity are common occurrences in people with gout.